Green Purchase Intention Among Public in Shah Alam - Mohd Sadad, Mahmud; Siti Noor Syahirah, Yusri (2017)
Purpose – This paper aimed to address the intention of public towards green product purchases, specifically in Shah Alam District. It also aims to determine the important factors that can influence more participation of public towards green product purchases. Methodology – A cross-sectional, quantitative method was employed with a sample size of 384 Shah Alam residents take part in the study. Findings – The pro-environmental behavior, price sensitivity and social influence significantly influenced public intention towards green product purchases. The results of the study implied that, public in Shah Alam are reported to be at a positive level and showed inclination for the public to form intention towards green product purchases. Originality/ Value – This study provide better insights to the involved stakeholders on factors that influence green product purchase intention among public.